The THE EFFECT OF DISTRIBUTION CHANNEL AND SERVICE QUALITY ON PURCHASING DECISION AT PT. MULTI ARTHA UNIVERSINDO MEDAN - Nazmi, Hendra (JEBIM Prima, 2019)
PT. Multi Artha Universindo Medan is a company engaged in the sale of socks of Mundo Brand. In its operation, the selling of socks Mundo brand decreased because customers decided not to buy goods at the company. The problems was caused by the bad distribution channels and the lack of service quality. The theories used in this research are those relating to Marketing Management, which deals with distribution channels, service quality, and purchase decisions. This research used quantitative approach. This is a quantitative descriptive research. The nature of this research is descriptive explanatory. Population and sample in this research were 123 regular customers of PT. Multi Artha Universindo Medan totaling 123 customers. Data collection techniques used were interviews, questionnaires, and documentation study. The data source of this research were primary and secondary data. The coefficient of determination showed that Adjusted R Square is 0.204 which means that 20.4% of customers purchase decision variable variation can be explained by variations in the distribution channels and the variable quality of service and the remaining 80.6% was affected by other factors not examined such as advertising, service quality, etc. The result of the hypothesis revealed that the distribution channel partially has a significant effect on purchase decisions of customers at PT. Multi Artha Universindo Medan. Service quality partially has a significant effect on purchase decisions of customers at PT. Multi Artha Universindo Medan. Distribution channels and quality of service simultaneously have a significant effect on customer decisions at PT. Multi Artha Universindo Medan. The conclusion of this study is that simultaneously and partially, distribution channels and service quality variables have a significant effect on the purchasing decisions of customers at PT. Multi Artha Universindo Medan. Keywords: Distribution Channels, Service Quality, Purchasing Decisions